Reimagining the Bible : the Storytelling of the Rabbis. - Schwartz, Howard (Oxford University Press, 1998)
This work explores how each successive phase of Jewish literature has drawn upon and reimagined the previous ones. Arguing that there is a continuity in Jewish literature which extends from the biblical era to our own times, this serves as a guide to the history of that literature and its genres.